A meta‐analysis of single HCV‐untreated arm of studies evaluating outcomes after curative treatments of HCV‐related hepatocellular carcinoma. (1st February 2017) - Cabibbo, Giuseppe; Petta, Salvatore; Barbàra, Marco; Missale, Gabriele; Virdone, Roberto; Caturelli, Eugenio; Piscaglia, Fabio; Morisco, Filomena; Colecchia, Antonio; Farinati, Fabio; Giannini, Edoardo; Trevisani, Franco; et al.
Abstract: Background & Aims: Determining risk for recurrence or survival after curative resection or ablation in patients with hepatitis C virus (HCV)‐related hepatocellular carcinoma (HCC) is important for stratifying patients according to expected outcomes in future studies of adjuvant therapy in the era of direct‐acting antivirals (DAAs). The aims of this meta‐analysis were to estimate the recurrence and survival probabilities of HCV‐related early HCC following complete response after potentially curative treatment and to identify predictors of recurrence and survival. Methods: Studies reporting time‐dependent outcomes (HCC recurrence or death) after potentially curative treatment of HCV‐related early HCC were identified in MEDLINE through May 2016. Data on patient populations and outcomes were extracted from each study by three independent observers and combined using a distribution‐free summary survival curve. Primary outcomes were actuarial probabilities of recurrence and survival. Results: Eleven studies met the inclusion criteria. Pooled estimates of actuarial recurrence rates were 7.4% at 6 months and 47.0% at 2 years. Pooled estimates of actuarial survival rates were 79.8% at 3 years and 58.6% at 5 years. Heterogeneity among studies was highly significant for all outcomes. By univariate meta‐regression analyses, lower serum albumin, randomized controlled trial study design and follow‐up were independently associated with higher recurrence risk, whereas tumour size and alpha‐foetoprotein levels were associated with higher mortality. Conclusions: This meta‐analysis showed that recurrence risk and survival are extremely variable in patients with successfully treated HCV‐related HCC, providing a useful benchmark for indirect comparisons of the benefits of DAAs and for a correct design of randomized controlled trials in the adjuvant setting.